Fracture mechanics analysis of defence hole system for a uniaxially loaded plate using boundary element method - Teo, Jonathan Jit Jon (Nanyang Technological University, 2024)
The main objective of this report is to analyse the outcome of defence hole systems on a main hole on a uni-axially loaded plate. The study utilises the BIE2DSRE-A computer program, which employs the Boundary-Element-Method (BEM) for stress analysis.